Neoinstitutional analysis of gender policies: Spanish cases (Global Journal of Human-Social Science, 2024)
This is a critical review on gender issue and its policies to understand and to evaluate the impact of the gender state interventionism with its costs failures paradoxes and other unwanted effects This review uses the theoretical and methodological frameworks from neoinstitutional approach Law Economics Public Choice Constitutional Economic etc to build bridges between Economy Law and Politics without confusion among the social spheres and under the principle of reality which rejects economic thaumaturgy political romanticism and state paternalism There is a historical-comparative review on the development of coercive implementation based on gender perspective and its agenda from a macro-view to a micro level focusing the attention on the Spanish case There is a final statement of its results to clarify what kind of incentives have been given the gender bills and policies the level of efficiency and institutional quality to solve social problems the risks of an endless agenda and other unwanted effects but foreseeable according to the principle of reality
Keywords: economic/state interventionism; gender issue; gender paradox; neoinstitutional approach